Fisetin reduces the senescent tubular epithelial cell burden and also inhibits proliferative fibroblasts in murine lupus nephritis - Ijima, Shogo; Saito, Yuki; Nagaoka, Kentaro; Yamamoto, Sena; Sato, Tsukasa; Miura, Norihiro; Iwamoto, Taiki; Miyajima, Maki; Chikenji, Takako S. (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease characterized by the involvement of multiple organs. Lupus nephritis (LN) is a major risk factor for overall morbidity and mortality in SLE patients. Hence, designing effective drugs is pivotal for treating individuals with LN. Fisetin plays a senolytic role by specifically eliminating senescent cells, inhibiting cell proliferation, and exerting anti-inflammatory, anti-oxidant, and anti-tumorigenic effects. However, limited research has been conducted on the utility and therapeutic mechanisms of fisetin in chronic inflammation. Similarly, whether the effects of fisetin depend on cell type remains unclear. In this study, we found that LN-prone MRL/lpr mice demonstrated accumulation of Ki-67-positive myofibroblasts and p15INK4B-positive senescent tubular epithelial cells (TECs) that highly expressed transforming growth factor β (TGF-β). TGF-β stimulation induced senescence of NRK-52E renal TECs and proliferation of NRK-49F renal fibroblasts, suggesting that TGF-β promotes senescence and proliferation in a cell type-dependent manner, which is inhibited by fisetin treatment in vitro. Furthermore, fisetin treatment in vivo reduced the number of senescent TECs and myofibroblasts, which attenuated kidney fibrosis, reduced senescence-associated secretory phenotype (SASP) expression, and increased TEC proliferation. These data suggest that the effects of fisetin vary depending on the cell type and may have therapeutic effects in complex and diverse LN pathologies.